2018
DOI: 10.3389/fnins.2018.00128
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Interactions With Lipid Rafts Related to Neuroprotection. Impact of Brain Ageing and Menopause

Abstract: Estrogens (E2) exert a plethora of neuroprotective actions against aged-associated brain diseases, including Alzheimer's disease (AD). Part of these actions takes place through binding to estrogen receptors (ER) embedded in signalosomes, where numerous signaling proteins are clustered. Signalosomes are preferentially located in lipid rafts which are dynamic membrane microstructures characterized by a peculiar lipid composition enriched in gangliosides, saturated fatty acids, cholesterol, and sphingolipids. Rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 245 publications
(286 reference statements)
1
52
0
Order By: Relevance
“…No significant abnormalities were found in female PD subjects [93]. Accordingly, it has been demonstrated that estradiol acts as homeostatic modulator of lipid rafts, thus preserving lipid balance in neuronal membrane microdomains [94].…”
Section: Dopaminergic Neurodegenerationmentioning
confidence: 91%
“…No significant abnormalities were found in female PD subjects [93]. Accordingly, it has been demonstrated that estradiol acts as homeostatic modulator of lipid rafts, thus preserving lipid balance in neuronal membrane microdomains [94].…”
Section: Dopaminergic Neurodegenerationmentioning
confidence: 91%
“…Recent papers have reviewed the neuroprotective actions of sex hormones and related synthetic steroids in different central nervous system (CNS) pathologies (Elkabes and Nicot, 2014;Engler-Chiurazzi et al, 2017: Baez-Jurado et al, 2018Céspedes Rubio et al, 2018;Bourque et al, 2019;Kulkarni et al, 2019;Sohrabji et al, 2019), including some of the specific molecular neuroprotective mechanisms activated by estradiol (Arevalo et al, 2015;Sohrabji, 2015;Labandeira-Garcia et al, 2016;Zup and Madden, 2016;Marin and Diaz, 2018;Thakkar et al, 2018) and the role played by glial cells on the neuroprotective mechanisms of the hormone (Karki et al, 2014;Acaz-Fonseca et al, 2016;Kipp et al, 2016;Martin-Jimenez et al, 2019). Another important issue that has been considered in recent years is the neuroprotective role of estradiol locally synthesized in the CNS (Pedersen et al, 2018;Brocca and Garcia-Segura, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work has shown that LRs exhibit pathological modifications with the progression of aging that are exacerbated in age-related neuropathologies (Marin et al, 2016, 2017; Canerina-Amaro et al, 2017; Diaz et al, 2018; Marin and Diaz, 2018). In particular, aged LRs exhibit altered raft lipidomic profiles and physicochemical properties that affect protein associations and may contribute to the cell-cell propagation of toxic α-syn aggregates (Marin et al, 2017; Rodriguez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%